Исследования раннесредневековых захоронений близ села Металловка в 2006 году (Нетайловский грунтовой могильник) - Аксенов, В.С. (Степи Европы в эпоху средневековья, 2009)
The paper considers 13 burials (##432-444) explored in 2006 at the Netailovka bunal ground of the Saltov culture. By a funeral ceremony the burials do not differ from a great bulk of' Proto-Bulgarian burials of the 8th-9th centuries AD in the south of Eastern Europe. However, the main specificity of burials of the burial ground is a big share of burials which not contain human remains, or the remains are presented by separate bones (fragments of skull and teeth). The new excavated burials in fact contain no human remains in grave pits which may be explained by the hydrotechnical situation in the burial ground area.